PENGARUH PENYEMPROTAN LARUTAN AIR GARAM TERHADAP DAYA TETAS TELUR ITIK HIBRIDA - Sutiyo R. A.; M. Wirapartha; G. A. M. K. Dewi (Animal Science Study Program, Faculty of Animal Husbandry, Udayana University, 2020)
This research hass been done in Mr. Budiono house which stay in Sidorejo Village, Rowokangkung District, Lumajang City, and this research in 1,5 mounth. This research progam is used Completely Randomized Design (CRD) with 4 treatment and 4 repetition and the contained in every repetition is 15 egg duck. P0 treatment as control (duck egg sprayed with warm water 38 oC), P1 (salt solution with dose 10 g/liter warm water 38 oC), P2 (salt solution with dose 20 g/liter warm water 38 oC), P3 (salt solution with dose 30 g/liter warm water 38 oC). The variable observed is egg weight, eeg indexs, fertility, egg shrinkage, DOD weight, mortality and hatchability. The result of research indicate the influence of spraying hybrid duck eeg with salt water to P0, P1 treatment and P3 not diffirent obvious (P>0,05) toward eeg weight, eeg index, fertility, eeg shrinkage and DOD weight but on P2 treatment real influence (P<0,05) toward mortality and hatchability. The conclusion of this research is influence of spraying hybrid egg duck with salt water on control consentration (P0), 10 g/liter warm water 38 oC (P1), and 30 g/liter warm water 38 oC (P3) hass not effect toward egg weight, egg index, fertility, shrinkage and DOD weight, but salt consentration 20 g/liter warm water 38 oC (P2) reduce embrio mortality during hatchability processed and increase egg hatchability. Keywords : hatchability, hatching machine, salt water spraying, duck egg